If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3v + -14 = 49 Reorder the terms: -14 + 3v = 49 Solving -14 + 3v = 49 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 3v = 49 + 14 Combine like terms: -14 + 14 = 0 0 + 3v = 49 + 14 3v = 49 + 14 Combine like terms: 49 + 14 = 63 3v = 63 Divide each side by '3'. v = 21 Simplifying v = 21
| 32-5x=12-9x | | 5u+4u=-27 | | 5+8x=-30+x | | 1/2x=2/3x-8 | | 4p^2-64q^2= | | 7g+16w=22.70 | | 9+5x=-7+x | | 11t+4(1-5t)= | | 8pqr+10prs= | | (M+4)(m+6)=0 | | (7-14)x-12-8/-4 | | 12y=1.44 | | a(x)+a+d(y)=7 | | -5deg+6deg= | | -2.5x=30.25 | | v=3*16*12 | | 15y=10 | | x^3+5x^2-2x-12=0 | | x-30x/100=35 | | 4z-19=5-8z | | v=4u-2 | | 4e-3=4-3e | | y=4-ln(x+2) | | 4(4)/16(4)2=x | | 3q=108-6q | | x=(x-1)+x | | e+2=8 | | 90-5h=4h | | 7z+(-13z)=x | | 8x+13=-43 | | 8n=96-4n | | dy=2d-ax |